2013
DOI: 10.1542/peds.2012-0765
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Developmental Screening in an Urban Setting

Abstract: Children who participated in a developmental screening program were more likely to be identified with developmental delays, referred to EI, and eligible for EI services in a timelier fashion than children who received surveillance alone. These results support policies endorsing developmental screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
149
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(170 citation statements)
references
References 36 publications
(27 reference statements)
4
149
0
8
Order By: Relevance
“…However, there is debate regarding this in recent research because with a performance below the cut off in two or more domains, the ASQ specificity increases [11][12][13] , while efficiency overall improves when the total score is considered 13,14 . Independent from the approach, it has been observed that when parents conduct the assessment, the search for possible development disorders significantly increases 2,15 , anticipating up to 30% referral increase among evaluated children 8,16 . The current evidence is unclear as most of the research corresponds to concurrent studies; therefore, there is a need to design prospective research that helps to define a deficit criterion with a real clinical impact.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is debate regarding this in recent research because with a performance below the cut off in two or more domains, the ASQ specificity increases [11][12][13] , while efficiency overall improves when the total score is considered 13,14 . Independent from the approach, it has been observed that when parents conduct the assessment, the search for possible development disorders significantly increases 2,15 , anticipating up to 30% referral increase among evaluated children 8,16 . The current evidence is unclear as most of the research corresponds to concurrent studies; therefore, there is a need to design prospective research that helps to define a deficit criterion with a real clinical impact.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Developmental assessments in the early years are regarded as important for identifying children at risk and for targeting early intervention. [7,8] As such, developmental tests at two years are widely used to assess neurodevelopmental outcomes and to ascertain eligibility for intervention services. [9] [10] For assessing the development of infants born very (< 32 weeks) and extremely (< 28 weeks) preterm, it is common practice to correct for gestation at birth up to two years of age.…”
mentioning
confidence: 99%
“…*indican diferencia estadística entre puntajes chilenos y de USA (p < 0,05). sarrollo en los programas de supervisión de salud, aumenta significativamente la pesquisa y derivación de niños con sospecha de déficit del Dsm 19,50 . La pregunta que nos hacemos es cuántos de esos niños están siendo sobre-identificados y sobre-derivados y cuáles podrían ser los efectos negativos de dicha práctica.…”
Section: Validación Nacional Asqunclassified
“…No obstante, se ha evidenciado que dicha estrategia es subjetiva y poco confiables para pesquisar dificultades más sutiles 6,17 . Por este motivo se recomienda complementar la evaluación clínica con pruebas de tamizaje estandarizadas a edades específicas o frente a factores de riesgo 7,18,19 . Cuando un niño fracasa en las pruebas de tamizaje, debería ser derivado a una evaluación diagnóstica integral, para decidir su incorporación en un programa de apoyo 20,21 .…”
unclassified
See 1 more Smart Citation